High-frequency laser therapy: a new alternative to physiotherapy in the treatment of cervical disk hernia - Kuculmez, Ozlem; Dündar Ahi, Emine; Cosar, Sacide Nur; Guzel, Sukran (Frontiers in Medicine, 2024)
High-frequency laser therapy has been recently started to be used in several musculoskeletal disorders, but there is still lack of evidence for usage of the device in neck pain. This study aims to compare effectiveness of physiotherapy, high-frequency laser and exercise therapy methods in treatment of pain in cervical disc herniation. It was a multicenter, randomized, controlled clinical trial. The patients aged between 18 and 65, suffering from neck pain, diagnosed cervical disc hernia were included in the study. Patients with a history of cervical surgery, rheumatism, cancer or pace-maker were excluded. The patients were randomized in 15 sessions physiotherapy, high-frequency laser or exercise therapy groups and evaluated with range of motion, Visual Analog Score, Neck Disability Index and Short Form Health Survey-36 before treatment, after treatment, in 1 st month and 3 rd month. P < 0.05 was considered statistically significant. Totally, 150 patients were analyzed. There was significant improvement in range of motion, Visual Analog Score, Neck Disability Index and Short Form Health Survey-36 scores in three groups after three months follow-up (p<0,05). The improvement was statistically greater in physiotherapy and high frequency laser therapy groups (p<0.05), but there was no significant difference between these two groups (p>0.05). The results in physiotherapy and high-frequency laser therapy groups were better than the exercise group. They may be alternatives to each other in cervical disc hernia treatment.